2019
DOI: 10.5539/hes.v9n4p133
|View full text |Cite
|
Sign up to set email alerts
|

Ten Salient Practices for Mentoring Student Research in Schools: New Opportunities for Teacher Professional Development

Abstract: This paper proposes ten salient practices of research mentoring activity in high school settings for teachers and technicians based upon survey and interview findings from 96 English and Scottish high school teachers from STEM disciplines, working in research collaborations with scientists. Mentoring high school research provides career development, with teachers identifying new aspects to their professional roles including 'teacher researcher', 'teacher scientist' and 'teacher mentor'. This study suggests the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Shanahan et al (2015) undertook a systematic review of existing literature and identified 10 salient practices of undergraduate research mentoring, which begin with strategic pre-planning and culminate with some form of dissemination of research. The practices have been applied across multiple contexts and disciplines, including interreligious studies (Allocco & Pennington, 2022), teacher development (Walkington & Rushton, 2019), theatre and dance (Shawyer et al, 2019), and Writing Studies (Moore et al, 2022).…”
Section: Mentoring In Undergraduate Researchmentioning
confidence: 99%
“…Shanahan et al (2015) undertook a systematic review of existing literature and identified 10 salient practices of undergraduate research mentoring, which begin with strategic pre-planning and culminate with some form of dissemination of research. The practices have been applied across multiple contexts and disciplines, including interreligious studies (Allocco & Pennington, 2022), teacher development (Walkington & Rushton, 2019), theatre and dance (Shawyer et al, 2019), and Writing Studies (Moore et al, 2022).…”
Section: Mentoring In Undergraduate Researchmentioning
confidence: 99%
“…Elon BrainCARE has also adopted the evidence-based mentoring framework (derived from the literature), hence referred to as the Salient Practices Framework as the way to provide high quality mentoring to students . These practices (also see Table 1; Center for Engaged Learning n.d.) have been demonstrated to be useful in a wide variety of disciplines (Moore et al 2020;Shawyer et al 2019;Walkington and Rushton 2019), as well as contexts such as global education (Hall et al 2018) and virtual environments ). These practices have also been found to be of great value in co-mentored experiences like Elon BrainCARE (Ketcham, Hall, and Miller 2017;Ketcham et al 2018) and that the implementation of these practices maps well into enhancing overall student well-being and building resilience .…”
Section: Salient Practices Framework For Undergraduate Research Mento...mentioning
confidence: 99%
“…Elon BrainCARE has also adopted the evidence-based mentoring framework (derived from the literature), hence referred to as the Salient Practices Framework as the way to provide high quality mentoring to students (Shanahan et al 2015). These practices (also see Table 1; Center for Engaged Learning n.d.) have been demonstrated to be useful in a wide variety of disciplines (Moore et al 2020;Shawyer et al 2019;Walkington and Rushton 2019), as well as contexts such as global education (Hall et al 2018) and virtual environments ). These practices have also been found to be of great value in co-mentored experiences like Elon BrainCARE (Ketcham, Hall, and Miller 2017;Ketcham et al 2018) and that the implementation of these practices maps well into enhancing overall student well-being and building resilience .…”
Section: Salient Practices Framework For Undergraduate Research Mento...mentioning
confidence: 99%